Inseguridad jurídica ante la indebida aplicación del habeas corpus en contra de las decisiones jurisdiccionales restrictivas de la privación de libertad. - Alvarez Aguinsaca, María José (2023)
The present Curricular Integration Work titled: "Legal Uncertainty in the Improper Application of Habeas Corpus against Restrictive Judicial Decisions on Deprivation of Liberty" arises from the interest in conducting a legal-doctrinal study due to the evident violation and improper application of the jurisdictional guarantee of habeas corpus, which is filed without complying with the necessary elements determined by law to submit this guarantee. In Ecuador, habeas corpus is an action that safeguards the right to freedom and related rights such as the life and personal integrity of individuals deprived of liberty, whether through a precautionary measure or a final judgment, guaranteeing and enforcing the Rule of Law. The conducted study and research demonstrate that the improper application of habeas corpus generates legal uncertainty when the lack of compliance is evident, primarily by lawyers, public servants, and administrators of justice, who have the duty to analyze whether the invocation of this guarantee is appropriate and not to give it momentum, considering that it entails an abuse of rights and legal insecurity. Finally, for this Curricular Integration Work, a methodology was used, consisting of materials, methods, and techniques that allowed its execution through surveys, interviews with legal professionals, and the study of specific cases that significantly contribute to the research. Thus, my work is concluded, and as a final product, the conclusions and recommendations are presented, which are intended to serve as an analysis for future students regarding habeas corpus.